IDENTIFYING DESTRUCTIVE EMOTION IN TOURISTâS EXPERIENCE JOURNEY - Ayu Dewi Maharani, Annisa
Tourism has evolved into a global sector that annually attracts millions of tourists from around the world and domestic travellers. The tourism industry in Indonesia is one of the most potential sectors for the nation's economy. Social media has a significant role in tourism marketing development. Social media opens an open space for consumers to interact and seek information about the actual state of the location. Besides that, tourists also tend to express and share their experiences through social media, such as making videos on YouTube, reviewing on Tripadvisor, or posting it on Twitter or Facebook. Tourist experience can trigger emotions (negative and positive), which will have an impact on post tourist experience, which affects revisit intention and tourist behavior after traveling. Therefore, this research aims to find out what kind of emotions arise in tourist experience, the causes and factors that influence it, its influence on tourists, and the response of service providers in dealing with critical incidents experienced by tourists. This study discovered that the emotions associated with tourist experiences could affect tourist place attachment, which leads to customer revisit intention and online behavior. Tourist emotions also arise from several factors, primarily service failure. Using thematic analysis and the typology of emotions listed in Colin Shaw's book DNA Customer Experience (NWOM). Aside from that, this study discovered that a collection of negative emotions categorized as a destroying cluster held the highest rank, with 'irritated' being the most common emotion felt by tourists. The research then discovered that the current state of the tourism industry in dealing with critical incidents tends to do nothing or make no change. This leads to tourists expressing themselves online or complaints by making video reviews and publishing on YouTube, which is categorized as NWOM.